Perception, Observation et Action - Lebon, F.; Guillot, A.; Collet, C.; Papaxanthis, C. (Movement & Sport Sciences - Science & Motricité, 2015)
Action observation is a predominant element of the perceptive register of humans and most animals, and substantially contributes to the development of motor abilities. Seeing another person moving activates the mirror neurons network, known as the neural basis of action understanding. In this review, we first discuss the central and behavioral responses underlying observation. Then, we identify the benefits and limits of (re)learning by observation. Finally, we present new approaches of action simulation, in which observation and other modalities - with internal or external origin - are associated.